What Is a “Fair” Price? Ethics as Sensemaking - Reinecke, Juliane; Ansari, Shaz (Organization Science, 2015)
Whereas the deliberative democracy approach to ethics seeks to bridge universalist reason and contextual judgment to explain the emergence of intersubjective agreements, it remains unclear how these two are reconciled in practice. We argue that a sensemaking approach is useful for examining how ethical truces emerge in equivocal situations. To understand how actors navigate through ethical complexity, we conducted an ethnographic inquiry into the multistakeholder practices of setting Fairtrade Minimum Prices. We offer three contributions. First, we develop a process model of ethics as sensemaking that explains how actors come to collectively agree on what is ethical in complex situations, even if no complete consensus arises. Second, our findings suggest that moral intuition and affect also motivate ethical judgment alongside moral reasoning. Third, an ethical sensemaking perspective explains some of the pitfalls actors confront in coping with ethical complexities in practice and how they attend to the challenges arising from stark inequalities in extreme contexts.